The Argonauts as a classic of Sociology: Malinowski and the recent history of New Economic Sociology - Wilkis, Ariel (2024)
This essay was presented at the tribute to Bronislaw Malinowski, 100 years after the publication of The Argonauts of the Western Pacific organized by the Department of Social Anthropology of the London School of Economics. Its objective is to reflect on the exchanges between sociology and economic anthropology in different academic contexts and how these dynamics generate different conditions for the field of the "new" economic sociology to recognize The Argonauts as a classic. Unlike the academies of the center of the global anthropological system, the interpretation that is presented here illuminates the favorable conditions that occurred in the Southern Cone - particularly through the influence of Brazilian anthropology and, especially, the role played by the Nucleus of Culture and Economy of the National Museum - in generating this recognition.